1998
DOI: 10.1083/jcb.143.6.1603
|View full text |Cite
|
Sign up to set email alerts
|

Role of Polo Kinase and Mid1p in Determining the Site of Cell Division in Fission Yeast

Abstract: The fission yeast Schizosaccharomyces pombe divides symmetrically using a medial F-actin– based contractile ring to produce equal-sized daughter cells. Mutants defective in two previously described genes, mid1 and pom1, frequently divide asymmetrically. Here we present the identification of three new temperature-sensitive mutants defective in localization of the division plane. All three mutants have mutations in the polo kinase gene, plo1, and show defects very similar to those of mid1 mutants in both the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
332
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 307 publications
(349 citation statements)
references
References 63 publications
13
332
0
4
Order By: Relevance
“…Medial-ring precursors start to accumulate at the cell center during the early stages of mitosis but only coalesce into a distinct ring during anaphase (Arai et al, 1998;Bähler et al, 1998a). Ain1p, Fim1p, and other actinbinding proteins such as Rng2p (Eng et al, 1998) may be involved in organizing the medial-ring precursors into a functional contractile ring (for review, see Bähler and Peter, 2000).…”
Section: Roles Of Ain1p and Fim1p In Cytokinesismentioning
confidence: 99%
“…Medial-ring precursors start to accumulate at the cell center during the early stages of mitosis but only coalesce into a distinct ring during anaphase (Arai et al, 1998;Bähler et al, 1998a). Ain1p, Fim1p, and other actinbinding proteins such as Rng2p (Eng et al, 1998) may be involved in organizing the medial-ring precursors into a functional contractile ring (for review, see Bähler and Peter, 2000).…”
Section: Roles Of Ain1p and Fim1p In Cytokinesismentioning
confidence: 99%
“…(B) The actin ring of plo1.ts18 mutant cells that have been incubated at the restrictive temperature for 3 h is misshapen and directs the deposition of a highly aberrant septum Targeted mutagenesis of a selected locus in Sz. pombe 593 in plo1.ts18 mutant cells was much larger than normal and appeared to randomly bisect the cell in a manner that was highly reminiscent of the plo1.1, plo1.24C and plo1.25 mutations reported by Bähler et al (1998a; Figure 3B). The ability of plo1.ts4 to use the F-actin ring to deposit septal material was severely compromised when the strain was grown in minimal medium (Tanaka et al, 2001); 4 h after the temperature was changed from 25 • C to 36 • C, 49% of cells contained multiple nuclei but had no septa (Tanaka et al, 2001).…”
Section: Phenotypic Analysis Of Plo1ts4 and Plo1ts18mentioning
confidence: 64%
“…Thus, cytokinesis was more sensitive than spindle formation to Plo1 levels. An additional Plo1 function was then identified in a screen for mutants that had defects in the location or structure of the actin ring that constricts to cleave the cell in two during cytokinesis (Bähler et al, 1998a). The positioning of the actin ring may therefore be more sensitive to Plo1 levels than the use of the ring to make a septum, and so this phenotype was not detected in the original analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This is considerably higher than that seen in clp1⌬ (0.5%) and pdk1⌬ (7%) mutants. The additive phenotypic effect upon combination of pdk1⌬ and clp1⌬ suggested that pdk1⌬ cells were partially defective in the assembly and/or function of the cell division apparatus.The similarities between the localization of Pdk1p and Plo1p (which regulates Mid1p localization; Bähler et al, 1998) and the finding that mid1 mutants, as with pdk1⌬ mutants, are delayed for actomyosin ring assembly (Wu et al, 2003), suggested that pdk1⌬ cells might be defective for Mid1p localization. Alternatively, pdk1⌬ cells might be defective for proper assembly and function of other actomyosin ring components.…”
mentioning
confidence: 99%
“…Gene products important for mitotic entry, mitotic progression, and cytokinesis have been identified from a number of genetic screens, as well as from reverse genetic approaches (Nurse et al, 1976;Hirano et al, 1986;Chang et al, 1996;Balasubramanian et al, 1998). Central to the regulation of mitosis and cytokinesis are the S. pombe polo-related protein kinase Plo1p (Ohkura et al, 1995;Bähler et al, 1998;Mulvihill et al, 1999) and members of the septation initiation network (SIN), a signaling pathway comprised of three protein kinases (Cdc7p, Sid1p, and Sid2p) and a GTPase (Spg1p) Rajagopalan et al, 2003). Members of the polo-kinase family are conserved across all eukaryotes (Nigg, 1998).…”
Section: Introductionmentioning
confidence: 99%